Biotransformation of nitrobenzene by bacteria containing toluene degradative pathways. - Haigler, B E (1991)
Nonpolar nitroaromatic compounds have been considered resistant to attack by oxygenases because of the electron withdrawing properties of the nitro group. We have investigated the ability of seven bacterial strains containing toluene degradative pathways to oxidize nitrobenzene. Cultures were induced with toluene vapor prior to incubation with nitrobenzene, and products were identified by high-performance liquid chromatography and gas chromatography-mass spectrometry. Pseudomonas cepacia G4 and a strain of Pseudomonas harboring the TOL plasmid (pTN2) did not transform nitrobenzene. Cells of Pseudomonas putida F1 and Pseudomonas sp. strain JS150 converted nitrobenzene to 3-nitrocatechol. Transformation of nitrobenzene in the presence of 18O2 indicated that the reaction in JS150 involved the incorporation of both atoms of oxygen in the 3-nitrocatechol, which suggests a dioxygenase mechanism. P. putida 39/D, a mutant strain of P. putida F1, converted nitrobenzene to a compound tentatively identified as cis-1,2-dihydroxy-3-nitrocyclohexa-3,5-diene. This compound was rapidly converted to 3-nitrocatechol by cells of strain JS150. Cultures of Pseudomonas mendocina KR-1 converted nitrobenzene to a mixture of 3- and 4-nitrophenol (10 and 63%, respectively). Pseudomonas pickettii PKO1 converted nitrobenzene to 3- and 4-nitrocatechol via 3- and 4-nitrophenol. The nitrocatechols were slowly degraded to unidentified metabolites. Nitrobenzene did not serve as an inducer for the enzymes that catalyzed its oxidation. These results indicate that the nitrobenzene ring is subject to initial attack by both mono- and dioxygenase enzymes.